Insight into the possible aetiologies of Blount's disease: a systematic review of the literature. Issue 4 (July 2020) - Banwarie, Radjen R.; Hollman, Freek; Meijs, Nandi; Arts, Jacobus J.; Vroemen, Pascal; Moh, Prosper; Staal, Heleen M.
Abstract : Blount's disease or bowed leg deformity, is a unilateral or bilateral growth deformity of the medial proximal tibia that leads to a tibial varus deformity. A distinction can be made in an early and late onset type. The disease seems to have a predisposition for certain descends. Since the first publication of Blount's disease, different hypotheses on the aetiology are proposed but no consensus exists. The objective of this study is to provide an overview of the available hypotheses on the aetiology of Blount's disease since its first description and assessment of the available level of evidence, the quality of evidence and the occurrence of bias supporting these individual hypotheses. A systematic search according to the PRISMA statement was conducted using PubMed, MEDLINE, EMBASE and the Cochrane Library using a broad combination of terminology to ascertain a complete selection. Proper MESH search criteria were formulated and the bibliographic search was limited to English and Dutch language articles. Articles with no mention of aetiology or a disease related to Blount's were excluded. Level of evidence and types of bias were assessed. Thirty-two articles that discuss the aetiology of Blount's disease were selected. A variety of hypotheses was postulated in these articles with most research in the field of increased mechanical pressure (obesity, early walking age) and race (descend). Blount's disease most likely has a multifactorial origin with influence of genetic and racial predisposition, increased mechanical pressure on the growth plate as a consequence of obesity or early walking age and possibly also nutrition. However, the exact aetiology remains unclear, the probable explanation is that multifactorial factors are all contributing to the development of Blount's disease. Histological research has shown that a disorganization of bone and cartilage structures on the medial side of the proximal tibial physis is present in patients with Blount's disease. Based on the available evidence on the aetiology of Blount's disease, we conclude that it is multifactorial. Most papers focus only on one hypotheses of Blount's disease occurrence and all are characterized as low level of evidence. There seems to be a preference for certain descends. Further research on especially genetic predisposition is needed to provide more insight in this factor of Blount's disease.